Silent brain injury following coronary angiography and revascularization in acute coronary syndrome: another reason to choose patients right. (26th April 2021) - Malinova, L; Tolstov, S; Lipatova, T; Denisova, T
Abstract: Funding Acknowledgements: Type of funding sources: None. Invasive coronary angiography (CAG) and revascularization remain the cornerstone of acute coronary syndrome (ACS) treatment. However silent brain injury (SBI) has been previously reported as a non-rare adverse event following coronary intervention. Several studies report serum NR2 antibodies (NR2AB) as a sensitive biomarker of ischemic brain injury suitable for express SBI diagnostics. Recently limited data are available regarding SBI per se in ACS. The relationship between NR2AB and chosen ACS treatment strategy is unclear. The purpose of the study: to evaluate the incidence and predictors of SBI after CAG and percutaneous coronary intervention in patients with ACS by serial measurement of serum NR2AB levels. Materials and methods: We perform local, open, continuous, stratified study involving patients underwent CAG with / without further coronary intervention due to recent ACS (n = 19) and ACS within 30 days (maximum) before recent admission (group of compare, n = 25). Serum NR2 antibodies concentration measured serially (before and no longer that 6 hours after the procedure) was used as SBI marker. Results: Endovascular coronary intervention in 15.9% was accompanied by NR2AB increase: the majority of NR2AB increase cases were observed in the group of compare (31.6% vs 5.5%). In those patients with prior ACS there was an increased risk of NR2AB level rise following PCI, that is, silent ischemic brain damage: HR 0.219 CI 0.171; 0.280, p = 0.049. Patients who underwent stenting of the coronary arteries were characterized by a more pronounced significant NR2 antibodies decrease after the procedure: -10.37 (-23.25; -7.65) vs -5.03 (-9.41; -1.79) % in ACS (p = 0.046) and -10.17 (-10.79; -10.20) vs -6.06 (-11.01; 4.68)% in the group of compare (p = 0.044), respectively. Conclusion: Coronary angiography and intervention in ACS is associated with a certain risk of silent ischemic brain injury (as has been assessed by NR2AB dynamics), increased in those cases where procedure was limited to CAG only. According to the results of the study, it seems reasonable to perform a preprocedure assessment of revascularization possibility to minimize risks of the possibility of ischemic brain injury.